2015
DOI: 10.1021/bi5011305
|View full text |Cite
|
Sign up to set email alerts
|

TtOmp85, a β-Barrel Assembly Protein, Functions by Barrel Augmentation

Abstract: Outer membrane proteins are vital for Gram-negative bacteria and organisms that inherited organelles from them. Proteins from the Omp85/BamA family conduct the insertion of membrane proteins into the outer membrane. We show that an eight-stranded outer membrane β-barrel protein, TtoA, is inserted and folded into liposomes by an Omp85 homologue. Furthermore, we recorded the channel conductance of this Omp85 protein in black lipid membranes, alone and in the presence of peptides comprising the sequence of the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 42 publications
4
28
0
Order By: Relevance
“…This was achieved by computing the partition function after exhaustive enumeration of the configuration states in the reduced state space, following ref [32, 34]. The energy of each configuration was evaluated using the Msip potential function, which incorporates both single residue burial energy and pairwise inter-strand interaction energies (see Materials and Methods for details) [32, 34, 38]. …”
Section: Resultsmentioning
confidence: 99%
“…This was achieved by computing the partition function after exhaustive enumeration of the configuration states in the reduced state space, following ref [32, 34]. The energy of each configuration was evaluated using the Msip potential function, which incorporates both single residue burial energy and pairwise inter-strand interaction energies (see Materials and Methods for details) [32, 34, 38]. …”
Section: Resultsmentioning
confidence: 99%
“…However, there does not appear to be a TamA homolog in D. radiodurans , indicating that DR_146T might act as a solo TamB. The presence of TamB in other bacteria lacking TamA has been reported, and the TAM system is suggested to have evolved from an original combination of TamB and BamA, which evolved into TamA in Proteobacteria by a later gene duplication event152938. Whether there was any interaction between TamB and BamA in D. radiodurans is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…What of the alternative scenario, wherein TamB interacts with BamA in these organisms? There have been functional analyses of BamA from organisms with a TamB–BamA operon ( Lenhart and Akins 2010 ; Lenhart et al 2012 ), or a TamB encoded on the genome separately from BamA, but again without TamA in the genome ( Nesper et al 2008 ; Tripp et al 2012 ; Estrada Mallarino et al 2015 ). Although these studies have not reported BamA–TamB interactions, neither have they excluded the formation of a TamB–BamA complex or more transient interaction between the proteins.…”
Section: Discussionmentioning
confidence: 99%